Characterising innovations in maternal and newborn health based on a common theory of change: lessons from developing and applying a characterisation framework in Nigeria, Ethiopia and India. Issue 4 (18th July 2019) - Makowiecka, Krystyna; Marchant, Tanya; Betemariam, Wuleta; Chaturvedi, Anuraag; Jana, Laboni; Liman, Audu; Mathewos, Bereket; Muhammad, Fatima B; Semrau, Katherine; Wunnava, Sita Shankar; Sibley, Lynn M; Berhanu, Della; et al.
Abstract : Government leadership is key to enhancing maternal and newborn survival. In low/middle-income countries, donor support is extensive and multiple actors add complexity. For policymakers and others interested in harmonising diverse maternal and newborn health efforts, a coherent description of project components and their intended outcomes, based on a common theory of change, can be a valuable tool. We outline an approach to developing such a tool to describe the work and the intended effect of a portfolio of nine large-scale maternal and newborn health projects in north-east Nigeria, Ethiopia and Uttar Pradesh in India. Teams from these projects developed a framework, the 'characterisation framework', based on a common theory of change. They used this framework to describe their innovations and their intended outcomes. Individual project characterisations were then collated in each geography, to identify what innovations were implemented where, when and at what scale, as well as the expected health benefit of the joint efforts of all projects. Our study had some limitations. It would have been enhanced by a more detailed description and analysis of context and, by framing our work in terms of discrete innovations, we may have missed some synergistic aspects of the combination of those innovations. Our approach can be valuable for building a programme according to a commonly agreed theory of change, as well as for researchers examining the effectiveness of the combined work of a range of actors. The exercise enables policymakers and funders, both within and between countries, to enhance coordination of efforts and to inform decision-making about what to fund, when and where.